Modelling and control design of the electrostatic linear comb actuator - Dzung Tien Nguyen; Nam Phuong Dao; Hoa Thi Thanh Lai (Institute of Advanced Engineering and Science, 2022)
Control design plays a major part in electrostatic linear comb actuator (ELCA) systems. Most existing control methods of ECLA mainly focus on traditional PID method. However, proportional–integral–derivative (PID) controller is only appropriate for the reference to be known as constant. In this article, the problem of establishing the dynamic model and designing the controller is investigated for ECLA working in the time-varying reference. The tracking effectiveness is constructed for ECLA systems based on the consideration of roots of the equivalent differential equation in tracking error model. Moreover, the convergence velocity is also tuned by changing the parameters in the presented control scheme. Simulation results guarantee the performance of the nonlinear control scheme as well as dynamic model to be established.